1996
DOI: 10.1152/ajpcell.1996.271.5.c1512
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate/chloride exchange and intracellular pH throughout preimplantation mouse embryo development

Abstract: HCO3-/Cl- exchanger activity, which regulates intracellular pH (pHi) in the alkaline range, has been shown to be present throughout preimplantation mouse embryo development and to be necessary for embryo viability. We have characterized HCO3-/Cl- exchange activity and its regulation of pHi throughout preimplantation development (1-cell, 2-cell, morula, and blastocyst stages). Embryos at each stage can recover from alkalosis. Recovery was dependent on external [Cl-], activated by increased pHi, and inhibited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…The expression levels of miR-125b in two-cell and four-cell embryos were significantly higher than that in morula and blastocyst stage (Figure 2A), which coincides with the transit of embryo from oviduct (high bicarbonate concentration) to the uterus (lower bicarbonate concentration) [42]. This suggested that the window for HCO 3 − -dependent miR-125b activation occurs from fertilization to four-cell stage but not in subsequent stages.…”
Section: Discussionmentioning
confidence: 87%
“…The expression levels of miR-125b in two-cell and four-cell embryos were significantly higher than that in morula and blastocyst stage (Figure 2A), which coincides with the transit of embryo from oviduct (high bicarbonate concentration) to the uterus (lower bicarbonate concentration) [42]. This suggested that the window for HCO 3 − -dependent miR-125b activation occurs from fertilization to four-cell stage but not in subsequent stages.…”
Section: Discussionmentioning
confidence: 87%
“…Baltz, unpublished). Similarly, HCO 3 À /Cl À exchange can be activated by alkalosis throughout preimplantation mouse embryo development (Baltz et al, 1991;Zhao et al, 1995;Zhao and Baltz, 1996;Cetinkaya and Erdogan, 2008), principally mediated by AE2 (Phillips and Baltz, 1999;Zhou et al, 2009). Similar findings have been reported for preimplantation embryos of human (Phillips et al, 2000), hamster (Lane et al, 1998(Lane et al, , 1999a, and bovine (Lane and Bavister, 1999).…”
Section: Acute Cell Volume Regulation By Inorganic Ion Transport In Ementioning
confidence: 99%
“…Detailed studies on embryo metabolism, examination of tubal fluid composition and other physiologic, molecular and biochemical insights have led to improved modifications of media formulations. This has resulted in several excellent culture media, both mono and sequential systems, giving laboratories multiple choices in terms of selection of ingredients such as glucose concentration or amino acid complement [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, despite the number of options in regard to substrate selection for embryo culture media for use within the laboratory incubator, the ability to select from a variety of pH buffers in handling media for use outside the incubator is extremely limited.…”
Section: Introductionmentioning
confidence: 99%
“…External pH of culture media (pHe) influences sperm binding and motility [7][8][9], oocyte maturation [10,11] and embryo development [12][13][14][15][16], though confounding factors such as bicarbonate and CO 2 levels exist. Improper intracellular pH (pHi) can impede sperm function [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation